A 52-to-67 GHz dual-core push–push VCO in 40-nm CMOS. Issue 7 (12th February 2018) - Issakov, Vadim; Rimmelspacher, Johannes; Trotta, Saverio; Tiebout, Marc; Hagelauer, Amelie; Weigel, Robert
Abstract: We present a continuously tunable 52-to-67 GHz push–push dual-core voltage-controlled oscillator (VCO) in a 40 nm bulk complementary metal–oxide–semiconductor (CMOS) technology. The circuit is suitable for 60 GHz frequency-modulated-continuous-wave radar applications requiring a continuously tunable ultra-wide modulation bandwidth. The LC-tank inductor is used to couple the two VCO cores. The fundamental frequency of the VCO can be tuned from 26 to 33.5 GHz, which corresponds to a frequency tuning range of 25%. The second harmonic is extracted in a non-invasive way using a transformer. The primary side acts simultaneously as a second harmonic filter. The VCO achieves in measurement a low phase noise of −91.8 dBc/Hz at 1 MHz offset at 62 GHz and an output power of −20 dBm. The VCO including buffers dissipates in the dual-core operation mode 60 mA from a single 1.1 V supply and consumes a chip area of 0.58 mm 2 .